Artistas aqui! : territórios poéticos construídos e vivenciados em espaços públicos e comunitários - Camargo, Carlos Augusto Nunes (2019)
Artists Here! more than a printed book that documents actions and artistic activations carried out in urban public spaces by students of a BA and Bachelor’s degree in Visual Arts, this article represents the valorization of dialogue and the collective construction of a new pedagogical practice that, from 2010 to 2017, shared and built new territories for teaching and acting in the arts